2018
DOI: 10.3390/app8081240
|View full text |Cite|
|
Sign up to set email alerts
|

Combined Process of Ozone Oxidation and Ultrafiltration as an Effective Treatment Technology for the Removal of Endocrine-Disrupting Chemicals

Abstract: Endocrine-disrupting chemicals (EDCs) in the secondary effluent discharged from wastewater treatment plants are of great concern when water reuse is intended. The combined process of ozone (O 3 ) and ultrafiltration (UF) is a promising EDC removal method. The removal efficiency of five EDCs using O 3 , UF and their combination were investigated and compared. The five EDCs were estrone, 17β-estradiol, estriol, 17α-ethynyl estradiol and bisphenol A, which are typically present in secondary effluent. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Ultrafiltration removal efficiency can be improved by combining it with other technologies like advanced oxidation processes, chlorination, and ozonation. The ultrafiltration-ozonation hybrid system employed by Si et al [135] was able to remove up to 99% of all endocrine disruptors under study (17β-estradiol, estriol, 17α-ethynylestradiol, and bisphenol A), compared to 46% and 70% reached using only ultrafiltration and ozonation, respectively. For the same reasons, membrane bioreactor is usually combined with nanofiltration or reverse osmosis process, thus improving the removal rate of contaminants such as bisphenol A, alkylphenols and carbamazepine [136,137].…”
Section: Removal Of Edcs From Watermentioning
confidence: 94%
“…Ultrafiltration removal efficiency can be improved by combining it with other technologies like advanced oxidation processes, chlorination, and ozonation. The ultrafiltration-ozonation hybrid system employed by Si et al [135] was able to remove up to 99% of all endocrine disruptors under study (17β-estradiol, estriol, 17α-ethynylestradiol, and bisphenol A), compared to 46% and 70% reached using only ultrafiltration and ozonation, respectively. For the same reasons, membrane bioreactor is usually combined with nanofiltration or reverse osmosis process, thus improving the removal rate of contaminants such as bisphenol A, alkylphenols and carbamazepine [136,137].…”
Section: Removal Of Edcs From Watermentioning
confidence: 94%
“…Therefore, the percentage of organic removal in some AOP-based treatment reactions can be determined by comparing the UV 254 absorbance at reactor effluent with its amount at reactor influent. Depending on the organic compounds, process, and operating conditions, ∆UVA 254 correlates to the amount of organic removal through a linear [158][159][160][161][162][163][164][165][166][167], S-shaped [168][169][170][171], logarithmic [172], exponential [172], linear biphasic [159,161,173], or other mathematic relation that need to be developed experimentally. In addition, the optimal UV absorbance for some organic compounds occurs at wavelengths other than 254 nm.…”
Section: Soft Sensorsmentioning
confidence: 99%
“…Similarly, Si et al [ 193 ] investigated the performance of combined ozonation and UF processes for the elimination of EDC pollutants in secondary sewage. The findings of the investigation showed that the combination of ozonation (O 3 ) and UF showed an excellent result, with almost 100% EDCs removal.…”
Section: Contemporary Techniques For the Removal Of Edcs From Various Water Sourcesmentioning
confidence: 99%